Combinatorial Low Dose Arsenic Trioxide and Cisplatin Exacerbates Autophagy via AMPK/STAT3 Signaling on Targeting Head and Neck Cancer Initiating Cells - Hu, Wei-Chun; Teo, Wan-Huai; Huang, Tung-Fu; Lee, Te-Chang; Lo, Jeng-Fan (Frontiers in Oncology, 2020)
Head and neck squamous cell carcinoma (HNSCC) is a highly lethal disease with high-level of epidemic both in the world and Taiwan. Previous studies support that head and neck cancer-initiating cells (HN-CICs), a subpopulation of cancer cells with enhanced stemness properties, contribute to therapy resistance and tumor recurrence. Arsenic trioxide (As2O3; ATO) has shown to be an effective anti-cancer drug targeting acute promyelocytic leukemia (APL). Combinatorial treatment with high dose of ATO and cisplatin (CDDP) exert synergistic apoptotic effects in cancer cell lines of various solid tumors, however, it may cause of significant side effect to the patients. Nevertheless, none has reported the anti-cancerous effect of ATO/CDDP targeting HN-CICs. In this study, we aim to evaluate the low dose combination of ATO with conventional chemo-drugs CDDP treatment on targeting HN-CICs. We first analyzed the inhibitory tumorigenicity of co-treatment with ATO and chemo-drugs on HN-CICs which are enriched from HNSCC cells. We observed that ATO/CDDP therapeutic regimen successfully synergized the cell death on HN-CICs with a Combination Index (CI) <1 by Chou-Talalay’s analysis in vitro. Interestingly, the ATO/CDDP regimen also induced exaggerated autophagy on HN-CICs. Additionally, this drug combination strategy also empowered both preventive and therapeutic effect by in vivo xenograft assays. Finally, we provide the underlying molecular mechanisms of ATO-based therapeutic regimen on HN-CICs. Together, low dose of combinatorial ATO/CDDP regimen induced cell death as well as exacerbated autophagy via AMPK-STAT3 mediated pathway in HN-CICs.